Parental perception on the effects of early exposure to anaesthesia on neurodevelopment. (1st November 2018) - Koh, J. H.; Daniel, P.; Bong, C. L.
Summary: Several studies have investigated the effects of general anaesthesia on neurodevelopment in children, with conflicting results. The potential for early general anaesthesia exposure to impact neurodevelopment in children may cause significant concern for parents. Administering a questionnaire in 200 parents, we aimed to explore their knowledge, concerns and perceptions, and determine factors which influence parents' willingness for their children to participate in relevant research studies. A significant proportion of parents (40%) were concerned that general anaesthesia may affect their child's neurodevelopment. Generally these concerns arose from the parents' own beliefs or preconceived ideas and only 25.5% had encountered prior information in this domain. Parents with children aged 2 years or younger, those whose children had previous general anaesthesia exposure, and those who had encountered information about potential neurodevelopmental effects were most likely to be concerned. The majority of parents (68%) would agree to participate in research studies, especially if they were able to receive the test results. Anaesthetists should pre‐emptively initiate discussions to address any potential misconceptions regarding the effects of general anaesthesia on neurodevelopment in children. 개요: 전신마취가 소아 뇌신경 발달에 미치는 영향에 대하여 조 사한 연구들은 서로 상반된 연구 결과를 보이고 있다. 소아에 서 어린 나이에 전신마취에 노출되는 것이 뇌신경 발달에 좋 지 않은 영향을 줄 수 있는 가능성은 부모들에게 큰 걱정거리 가 될 수 있다. 연구자들은 200명의 부모에게 설문을 하여 마 취제의 뇌독성에 관한 부모의 지식, 걱정과 인식 정도를 평가 하고, 관련된 연구 참여에 영향을 줄 수 있는 인자를 확인하 고자 하였다. 상당수의 부모들은(40%) 전신마취가 자녀의 뇌 신경 발달에 영향을 줄 수도 있음을 걱정하고 있었다. 이러한 걱정은 일반적으로 부모들 자신의 믿음이나 선입견에 기인한 것이고, 단지 25.5%의 부모들이 이러한 영역의 정보를 미리 접 하였다고 한다. 2세 이하의 자녀, 과거 전신마취 경험이 있는 자녀를 갖는 경우, 전신마취의 뇌신경 발달에 영향을 줄 수 있 는 가능성에 관한 정보를 접한 경우, 부모들은 전신마취에 관 하여 더 걱정하는 것으로 나타났다. 대부분의 부모들(65%)은 테스트 결과를 받을 수 있다면 관련된 연구에 참여하는 것을 동의하였다. 마취과 의사는 소아에서 전신마취의 뇌신경 발달 영향에 관한 있을지도 모르는 오해를 풀기 위하여 선제적으로 토론을 시작해야 할 것이다.